A Study Of Prevalence Of Thyroid Dysfunction In Type 1 Diabetic Children In A Tertiary Care Hospital From A Sub-Urban Population (Journal of Pharmaceutical Negative Results, 2022)
Background: Type 1 diabetes mellitus (T1DM) is an autoimmune disease resulting in insulin deficiency1. This also predisposes these individuals to other autoimmune diseases such as thyroid disease,2 celiac disease and adrenal insufficiency. Our study focus on thyroid changes in type1 diabetic children in Indian population .Aim: To assess the prevalence of thyroid dysfunction in type 1 diabetic children in a tertiary care hospital from a sub-urban population.Materials and Methods:It is a cross sectional study done on 142 children with type 1 diabetes attending pediatric OPD . All necessary investigations were done and data were collected .SPSS 24was used for statistical analysis of resultsResults:Higher prevalence of thyroid dysfunction was seen in children with type 1 diabetes in our study .Conclusion:The reason for hypothyroidism in type 1 diabetics is mostly auto-immune origin. So screening of thyroid function and thyroid antibodies is very important in all type 1 diabetic children for better prognosis and prompt treatment.